(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
All food products, including the products of the water resource, must meet the human needs for a complete diet, namely, energy and valuable substances. That is why it is so important to control the quality of these products. The article examines the nutritional and biological value of caviar of the perch family Percidae. The chemical composition of caviar is not constant and significantly depends on the type, physiological state, age, sex, habitat of fish and other factors.